Patients' perceptions and preferences of oral and maxillofacial surgeons in a university dental hospital - Gökhan Gürler; Çağrı Delilbaşı; İpek Kaçar (Istanbul University, 2018)
Purpose There is a lack of information regarding the dental patient's point of view of oral and maxillofacial surgeons (OMFSs). The aim of this study was to evaluate the perceptions and preferences of a group of university dental hospital patients for OMFSs. Materials and methods This study was based on patients' self-assessment using a questionnaire. A total of 530 patients were enrolled for the study. The patients' preferences regarding the surgeons' age, gender, religion, race and experience were determined and compared statistically. Results A total of 506 questionnaires were considered as complete and used in the analysis. Female patients preferred female practitioner more than male patients did (p=0.002), but no significant difference was found between male and female patients regarding preference for the age (p=0.464), ethnicity (p=0.926) and religion (p=0.261) of the OMFS. The educational status of the patients did not have an effect on the gender preference for the OMFS (p=0.114); however, educational status significantly affected the preferences for the ethnicity and religion of the practitioners (p=0.001). Conclusion Today patient expectations and perceptions take place in post graduate education programs. In this study we determined a wide range of different factors for choosing an OMFS. The diversity of these factors may affect the quality of the health service and thus must be considered in determining the content of oral and maxillofacial curriculum.